Metabarcoding of soil environmental DNA replicates plant community variation but not specificity. Issue 4 (22nd February 2022) - Barnes, Christopher James; Nielsen, Ida Broman; Aagaard, Anne; Ejrnæs, Rasmus; Hansen, Anders Johannes; Frøslev, Tobias Guldberg
Abstract: While metabarcoding of plant DNA from their environment is an exciting method that can supplement inventorying of live plant species, the accuracy and specificity has yet to be fully assessed over complex continuous landscapes. In this work, we evaluate plant community profiles produced via metabarcoding of soil by comparing them to a morphological survey. We assessed plant communities by metabarcoding of soil DNA in 130 sites along ecological gradients (nutrients, succession, moisture) in Denmark using chloroplast trn L region (10–143 bp) primer set and compared the resulting communities to communities produced with a longer nuclear ITS2 region (~216 bp) and a morphological survey. We found that the community variation observed within the morphological survey was well represented by molecular surveys, with significant correlation with both community composition and richness using both primer sets. While the majority of the ITS2 sequences could be assigned to species (over 80%), we had less success with the trn L sequences (70%), which was only possible after restricting the reference database to local species. We conclude that the community profiles produced by metabarcoding can be highly effective in performing large‐scale macroecological studies. However, the discovery rates and taxonomic assignments produced via metabarcoding remained inferior to morphological surveys, but manual curation of databases improves the specificity of assignments made by the trn L primers, and improves the accuracy of the assignments made with the ITS2 primers. Finally, we suggest that a greater percentage of named diversity would be recovered by increasing soil sampling with the use of additional universal primer sets. Abstract : While metabarcoding of plant DNA from their environment is an exciting method that can supplement inventorying of live plant species, the accuracy and specificity has yet to be fully assessed over complex continuous landscapes. This work shows that the metabarcoding of plant DNA from soil produces community profiles that are comparable to a morphological survey. However, the molecular approaches failed to recover a substantial proportion of named plant diversity, which can be partially compensated via database curation.